2007
DOI: 10.1201/9781420013719.ch10
|View full text |Cite
|
Sign up to set email alerts
|

Algebraic Deadlock Avoidance Policies for Sequential Resource Allocation Systems

Abstract: As many contemporary technological applications move to operational modes of more extensive and flexible automation, there is a rising need to design and control the underlying resource allocation not only for efficiency, but also for logical correctness and internal consistency. The material presented in this chapter offers a unifying and comprehensive treatment of a class of policies that have been proposed as an effective and efficient solution to this emerging class of logical control problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…Furthermore, even in its feasible cases, practical experience has shown that it is very demanding computationally and it results in PN representations of the maximally permissive LES that are much larger than the PN modeling the original RAS. The reader can find an extensive coverage of all these past developments in [33], [29], [25], [21], and the references cited therein.…”
Section: Pervision (Les)mentioning
confidence: 99%
“…Furthermore, even in its feasible cases, practical experience has shown that it is very demanding computationally and it results in PN representations of the maximally permissive LES that are much larger than the PN modeling the original RAS. The reader can find an extensive coverage of all these past developments in [33], [29], [25], [21], and the references cited therein.…”
Section: Pervision (Les)mentioning
confidence: 99%
“…One could guarantee deadlock-freeness by serializing all threads, which of course defeats the purpose of concurrent programming. Maximal permissiveness is an important reason why we employ SBPI rather than the algebraic methods described in [28], [29].…”
Section: B Challenges and Limitationsmentioning
confidence: 99%
“…When a deadlock occurs, it is detected and then the system is put back to a deadlock-free state. Deadlock avoidance 4,11,12,15,48,53,54,56,57,73,106,107,109,[122][123][124][125][126][127][128][129][130][131][132][133][134][135][136]319 is a resources allocation mechanism, behind which an online control policy is used to make a correct decision to proceed among the feasible evolutions. Deadlock prevention 6,49,71,72,75,77,82,91,[95][96][97][98]103,111,[137][138][139][140][141][142]…”
Section: Introductionmentioning
confidence: 99%